Evaluación agronómica y nutricional de 6 gramíneas forrajeras producidas en la finca Santa Inés, cantón Montufar, provincia del Carchi - Paspuel Sánchez, Alex Javier (2023)
Rye grass is a grass that adapts very well to a wide variety of soils, it is a dense grass with a lot of foliage, excellent flavor and good acceptance by animals, which consume it even in the flowering state, making it one of the one of the most used in the province of Carchi for bovine feeding. Given the adverse effects caused by climate change, new varieties of Rye grass have been generated that seek better agronomic characteristics, greater resistance and biomass production with high nutritional levels that must be evaluated under local conditions. The objective of this research was to evaluate during 3 consecutive cuts the behavior of 6 forage grasses under agroclimatic conditions in the Carchi province, Montufar canton on the Santa Inés farm, through field and laboratory tests as an alternative for animal feeding. The germination percentage, plant height, cutting days, percentage coverage were evaluated\; while the nutritional variables were dry matter (%), fiber (%), protein (%), and energy (Mcal) in the PUCES I laboratory. The experimental design was randomized complete blocks with six treatments. After data collection, it was evidenced that the T6 corresponding to the Pastoral variety was the best in bromatological aspects, obtaining the following results: DM 21.11%, fiber 18.43%, protein 19.21%, and energy 4.59 Mcal, while in agronomic aspects there are treatments that excel in certain characteristics, demonstrating great agronomic potential in the future. Analysis of variance (ANOVA) was performed on the data and the Tukey test was applied at 5%, for this the INFOSTAT 2020 software was used.